"But we still try": affective labor in the corporate mommy blog. Issue 1 (2nd January 2019) - Cummings, Kelsey
Abstract: This article studies three "mommy blogs, " online platforms catering to (in these cases) American mothers of various sub-demographics, through an affective labor framework. Using digital labor and Althusserian subject formation to inform my reading of the common rhetorical gestures made in these blogs, I ask how they conceive of their readership and contributors. I argue that mommy blogs should be understood as sites of digital labor because of the ways in which their publishing conditions and rhetorics establish labored expectations of the "mommy" subject. Contestations of the nature of affective labor in motherhood are reflected by anxieties around digital labor, which play out via ideological conflicts that manifest rhetorically in the blogs under discussion. This analysis is informed by affect theory, Althusser and Butler's work on subject formation, and the existing feminist literature on digital labor and the mommy blog.